2002
DOI: 10.1667/0033-7587(2002)157[0175:trsfts]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Raman Spectroscopy for the Study of Radiation Damage: Brain Irradiation of Mice

Abstract: Radiotherapy is routinely employed in the treatment of head and neck cancers. Acute cell death, radiation-activated chemical cascades, and the induction of genes coding for protective factors like cytokines are considered to be the major processes involved in radiation damage and repair. It should be possible to follow these processes by monitoring the biochemical interactions initiated by radiation. We have carried out Raman spectroscopy studies on tissue from mice subjected to brain irradiation to identify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
137
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(137 citation statements)
references
References 13 publications
0
137
0
Order By: Relevance
“…We have explored classical spectral deconvolution analysis to understand biochemical differences due to radiation induced effects in mouse models 31 and oral tissues. 25,32 We have also explored this approach for autofluorescence spectra of breast 33 and oral tissues.…”
Section: Curve Fitting Of Breast Raman Spectra 541mentioning
confidence: 99%
“…We have explored classical spectral deconvolution analysis to understand biochemical differences due to radiation induced effects in mouse models 31 and oral tissues. 25,32 We have also explored this approach for autofluorescence spectra of breast 33 and oral tissues.…”
Section: Curve Fitting Of Breast Raman Spectra 541mentioning
confidence: 99%
“…Such studies continue to contribute to the understanding of the interaction mechanisms between radiation and key molecular species and structures within the cell [48][49][50][51]. These investigations have since evolved to Raman spectroscopic studies of the effects of in-vitro proton irradiation of excised tissues [52], and radiotherapeutically irradiated (γ-radiation) tissue specimens [53][54][55]. Other studies with bacteria have investigated the effects of γ-radiation on Deinococcus radiodurans [56], Kocuria rosea [57]and Micrococcus luteus [58] with FTIR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…2A). Raman bands of the mean spectrasuch as bands of phenylalanine (C-C aromatic ring) at 1001 cm -1 [32], lipids/proteins (CH 2 bending mode) at 1448 cm -1 [33], amide I at 1657 cm -1 [34] and lipids (CH stretch of lipids) at 2924 cm -1 [35] -were identified and assigned. We found that the Raman band at 2924 cm in intensity with increased passage number.…”
Section: Resultsmentioning
confidence: 99%
“…It has already been shown that there is a relation between cell aggregation and enhanced cartilaginous tissue formation [34][35]. The rationale behind these methods are: (1) that chondrocyte phenotype is stabilized in the aggregate; and (2) that tissue engineered cartilage can be created without supportive carriers, such as polymers or gels in the form of a scaffold [36][37].…”
Section: Articular Cartilage and Cartilage Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation